(untitled) (Comunicação & Inovação, 2017)
This article discusses three strategies in the field of communication for the development and social change addressed to the communicational empowerment of technicians, rural producers and local leaders. The initiatives take place in the states of Ceará, Piauí and Rio Grande do Norte, based on participative methodologies with strong use of social networks and on workshops on communicative practices as a way of reorienting the flow of information and knowledge. Our goal is to provide participants with skills and make them capable of transmitting, and not just receive the exchange of knowledge between research institutions, technical assistance, rural extensions and farmers.